The Imaginal Characters of Cincticostella gosei (Allen, 1975) linking the genus Cincticostella Allen, 1971 to Ephacerella Paclt, 1994 (Ephemeroptera: Ephemerellidae) - Zhang, Min; Li, Wen-Juan; Ying, Xiao-Li; Zhou, Chang-Fa (Zootaxa, 2021)
The imagos of Cincticostella gosei (Allen, 1975), which were reared from mature nymphs in Spring 2021 in China, are described in detail for the first time, along with the eggs. Junior synonyms Ephemerella nigromaculata Xu et al., 1980 and Ephemerella tianmushanensis Xu et al., 1980 are confirmed upon new materials and types. Compared to congeners, the males of C. gosei have dark tibiae and gently curved forceps. In addition, the nymphs of this species are redescribed and photographed in detail. Morphologically, the nymph can be identified by pairs of smaller tergal spines on the abdomen and lack of maxillary palp. The smaller body size is also helpful to its identification among Chinese Cincticostella species. The characters of C. gosei seem like those of Ephacerella Paclt, 1994 in smoothly bent forceps and narrowed penes from base to apex.